The Intimacy of Fatherhood - Hemming, Patrick (2016)
The author presents a personal narrative of his experience as a father of church dealing with the Mormon church history, church's influence on fatherhood, and family responsibilities.
Keywords: Fatherhood; Mormon Church -- History; Religious Aspects